'A Faithful and Wise Servant'? Innocent III (1198–1216) Looks at his Household. (4th January 2016) - Bolton, Brenda
Abstract : Arriving at the Lateran on 8 January 1198, officials conducted Innocent III (born Lotari dei Conti di Segni) ceremonially to his apartments within the palace, there to rest, pray and dine.' Foremost amongst his concerns was the household, last reformed by Gregory I (590–604). Whilst Innocent clearly adopted Gregory as his model, both for the shaping of his personal life as pope and for his understanding of the papal office, the young pope's efforts to make his household as exemplary as that of his great predecessor have not received the attention they undoubtedly deserve. Gregory's finest Life, composed c .875 by John, a Roman deacon, uses material from the early vitae, thus avoiding the 'scrappy and grudging' biography of the Liber pontificalis . Instead, John draws extensively on Gregory's letters and the crumbling but then still extant papyrus volumes of the Registrum to demonstrate how this pope transformed his household into monastery, hospice and refuge. Three centuries later, the author of the Gesta Innocentii or Deeds of Innocent III could do no better than to adapt portions of John's Life to highlight reforms not evidenced since the sixth century Like Gregory, Innocent wished to restore the ideas of the apostolic age to the Church. And where better to begin the spiritual renewal than within a reformed household? His inaugural sermon as pope on St Matthew's faithful and wise servant accords perfectly with John the Deacon's view of Gregory as paterfamilias Domini, head of the Lord's household. Innocent, therefore, regarded the household not only as a metaphor for the congregation of the faithful but also, like Gregory before him, as a model to be used by missionaries to plant and nurture the faith throughout Christendom. Whilst the ongoing conversion of Livonia would provide Innocent with a rare opportunity to inculcate the Christian household within a pagan society, in the Patrimony of St Peter he diverged from Gregory's path by purposeful itineration with his familia, thus initiating a public role for the household.